Perancangan Sistem Informasi Manajamen Pelayanan Pasien Rawat Jalan Berbasis Web Di Puskesmas - Miftakhudin, Mokh; Dwi Kurniawan , Safar (Applied Information Technology and Computer Science (AICOMS), 2024)
The Web-Based Outpatient Service Management Information System at Community Health Centers is an application designed to support outpatient service processes for patients seeking medical check-ups at health centers. This application aims to assist health center staff in providing better services to patients. It also serves as a platform for storing patient data related to medical check-ups conducted at the health center. The application is developed using Hypertext Preprocessor (PHP) as the programming language, the Waterfall development method, and Unified Modeling Language (UML) for design modeling. The study resulted in a web-based application that allows health center staff to manage patient data, examiner data, queues, patient medical records, visits, prescriptions, medications, patient referral information, payment data, and generate necessary reports to support patient services.